2012
DOI: 10.1007/s10461-012-0165-6
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Heterosexual Condom Use among Homeless Men

Abstract: This study uses an event-based approach to examine individual, relationship, and contextual correlates of heterosexual condom use among homeless men. Structured interviews were conducted with a predominantly African American sample of 305 men recruited from meal lines in the Skid Row area of Los Angeles. Men reported on their most recent heterosexual event involving vaginal or anal intercourse. Adjusting for demographic characteristics only, condom use was more likely when men had higher condom use self-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Even when one of the steady partners has been identified with a sexually transmitted disease (STD), including HIV, or when one of the partners is known to have had sex with individuals who may have engaged in unsafe sex with others, condom use remains perceived as in violation with the expectations and nature of the steady partnership (Corbett et al, 2009). Perceptions of and commitment to a steady sex partner appear to overwrite potential motives in favor of condom use, especially among women (De Visser & Smith, 2001; Tucker et al, 2012). …”
Section: Sex Partner Typesmentioning
confidence: 99%
“…Even when one of the steady partners has been identified with a sexually transmitted disease (STD), including HIV, or when one of the partners is known to have had sex with individuals who may have engaged in unsafe sex with others, condom use remains perceived as in violation with the expectations and nature of the steady partnership (Corbett et al, 2009). Perceptions of and commitment to a steady sex partner appear to overwrite potential motives in favor of condom use, especially among women (De Visser & Smith, 2001; Tucker et al, 2012). …”
Section: Sex Partner Typesmentioning
confidence: 99%
“…In the scientific literature, evidence has been accumulating to suggest that various subgroups of African American adults may have lower overall levels of condom use self-efficacy, thereby elevating their risk for contracting HIV and other STIs. This has been found to be true for African Americans who are crack users [20], homeless [21], adolescent females [22], juvenile offenders [23], rural-dwelling women aged 50 or older [24] and HIV-positive men who have sex with men [25]. …”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising as increased odds of unprotected sex (or lower odds of condom use) with a primary or steady partner have been reported in the literature (Grangeiro et al, 2012;Kilbourne et al, 2002;Tucker et al, 2010;Tucker et al, 2013). Moreover, Stein, Nyamathi, Ullman and Bentler (2007) found that marriage and lower condom use were significantly correlated in their confirmatory factor analysis, but not in their predictive model.…”
Section: Chapter 4 Discussionmentioning
confidence: 69%